Simulation of Precise Automatic Radio Frequency GroundStation Tracking For S-Band Satellites - Wajirakumara, Akila (Luleå tekniska universitet, Rymdteknik, 2021)
Satellites are often known for possessing invariable motion causing its apparent position to drift in the sky from the perspective of a ground station. If these irregular drifts are not compensated, the performance of the communication link would be greatly affected. Hence, the satellite motion has to be tracked by the ground station antenna. Arctic Space Technologies is a company based in northern Sweden that focuses on highly reliable and secure satellite data handling solutions; main with S-Band satellites in the Low Earth Orbit (LEO). This thesis consolidates a comprehensive research to implement a robust approach for ground stations to establish a secure connection for optimum satellite communication performance. The implementation will be conducted in the form of a software simulation using MATLAB and SIMULINK. The system proposed in this thesis relies on Two Line Elements (TLE) to obtain the parameters for the calculation of the orbital motion of the satellites and providing the azimuth and elevation angles for the antenna to point towards. However, although TLE data are fairly accurate; LEO satellites have a very small time period passing over a ground station for signals to be received and thus it is vital to ensure maximum signal strength is received for optimum performance in satellite communication. In order to do so, a Kalman filter is incorporated to reduce the antenna’s pointing error by adjusting the estimated trajectory in real time and manoeuvre the ground station accordingly. This thesis uncovers through a theoretical review and simulation that accumulates and ensures the investigation of the primary data from the TLE; the main elements affecting the current situation and rectifying them to a certain extent using control systems. It furnishes with guidelines on how Radio Frequency (RF) signals from S-Band LEO satellites can be effectively communicated through a parabolic reflector as a ground station.